2013
DOI: 10.1007/s11051-013-2201-5
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of thermodynamic balance between cluster isomers and statistical model for predicting isomerization rate

Abstract: -By molecular dynamics simulations and free energy calculations based on MonteCarlo method, the detailed balance between Pt cluster isomers was investigated. For clusters of n≤50, stationary equilibrium is achieved in 100 ns in the canonical ensemble, while longer time is needed for n>50. Then, a statistical mechanical model was built to evaluate unimolecular isomerization rate and simplify the prediction of isomer formation probability. This model is simpler than transition state theory and can be easily appl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In our previous work, we found that for Pt cluster isomers the prediction of free energy criterion is in good agreement with equilibrium molecular dynamics (MD) simulations. [14] However, in the study of C clusters [5,15,16] we found that for C 36 isomers the free energy criterion can only roughly give the differences in formation probability among cage, bowl, and sheet isomers, but fails to quantitatively predict the formation probability of each isomer. [17] In this case, we even develop a time-going-back method [18] and a statistical model [19] to predict C isomer formation probability.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we found that for Pt cluster isomers the prediction of free energy criterion is in good agreement with equilibrium molecular dynamics (MD) simulations. [14] However, in the study of C clusters [5,15,16] we found that for C 36 isomers the free energy criterion can only roughly give the differences in formation probability among cage, bowl, and sheet isomers, but fails to quantitatively predict the formation probability of each isomer. [17] In this case, we even develop a time-going-back method [18] and a statistical model [19] to predict C isomer formation probability.…”
Section: Introductionmentioning
confidence: 99%